To be or not to be ... self-employed: Impact of family background on women entrepreneurs - Caroline Ruiner (Leadership, Education, Personality. An Interdisciplinary Journal, 2019)
This paper aims to reveal entrepreneurs' patterns of perceiving, thinking, and acting as a basis for entrepreneurial behavior and, thus, highlights the relevance of the entrepreneurs' embodied cultural capital. The empirical data presented in this article are based on a qualitative empirical study of twenty women entrepreneurs, their families (mothers, fathers, and siblings) and their partners, in total 100 interviews. The entrepreneurs interviewed have in principle similar institutionalized cultural capital, as all are academics and all have started a business in the fields of education, consulting, or media. However, they differ essentially in how they manage their self-employment in the sense of doing entrepreneurship. The results show that habitual patterns of perceiving, thinking, and acting differ which helps to understand entrepreneurial behaviour. In this sense, the process of starting a business can be regarded as a demonstration of the habitus at work.
Keywords: 330; Embodied cultural capital; Self-employment; Entrepreneurial behavior; Habitus